2018
DOI: 10.1002/adma.201801745
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Silicide Surface Enrichment: A Solution to Lithium Metal Battery

Abstract: The propensity of lithium dendrite formation during the charging process of lithium metal batteries is linked to inhomogeneity on the lithium surface layer. The high reactivity of lithium and the complex surface structure of the native layer create "hot spots" for fast dendritic growth. Here, it is demonstrated that a fundamental restructuring of the lithium surface in the form of lithium silicide (Li Si) can effectively eliminate the surface inhomogeneity on the lithium surface. In situ optical microscopic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
129
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(132 citation statements)
references
References 74 publications
2
129
0
1
Order By: Relevance
“…[9] Owing to the multi-component solid electrolyte interphase (SEI) layer and uneven anode substrate, inhomogeneous lithium-ion flux is formed at the electrode/electrolyte interface, leading to nonuniform lithium eletrodeposition on the metal surface. These methods include doping electrolyte additives (Li halide, [12] ionic liquid, [13] and Cs +[14] ) and coating artificial SEIs (Li 3 PO 4 , [15] Cu 3 N, [16] LiF, [17] and Li alloy [18][19][20] ) on Li anode. This dendrite formation behavior can be much severe at high current densities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Owing to the multi-component solid electrolyte interphase (SEI) layer and uneven anode substrate, inhomogeneous lithium-ion flux is formed at the electrode/electrolyte interface, leading to nonuniform lithium eletrodeposition on the metal surface. These methods include doping electrolyte additives (Li halide, [12] ionic liquid, [13] and Cs +[14] ) and coating artificial SEIs (Li 3 PO 4 , [15] Cu 3 N, [16] LiF, [17] and Li alloy [18][19][20] ) on Li anode. This dendrite formation behavior can be much severe at high current densities.…”
mentioning
confidence: 99%
“…These methods include doping electrolyte additives (Li halide, [12] ionic liquid, [13] and Cs +[14] ) and coating artificial SEIs (Li 3 PO 4 , [15] Cu 3 N, [16] LiF, [17] and Li alloy [18][19][20] ) on Li anode. These methods include doping electrolyte additives (Li halide, [12] ionic liquid, [13] and Cs +[14] ) and coating artificial SEIs (Li 3 PO 4 , [15] Cu 3 N, [16] LiF, [17] and Li alloy [18][19][20] ) on Li anode.…”
mentioning
confidence: 99%
“…The graphite-SiO 2 bilayer prevents any side reactions between Li and electrolyte due to its electrochemical and mechanical stabilities (see Figure S4 in the Supporting Information for details). [42] As a comparison, the bare Li shows unstable SEI formation, undesired side reactions, and dendrite growth, which consumes a significant amount of electrolyte. [40] In contrast, the bare Li reacts with electrolyte responsible for the formation of thick carbonaterich unstable SEI and an insulating surface.…”
Section: Resultsmentioning
confidence: 99%
“…A full Li–S cell consisted of a 2D‐MoS 2 protected Li anode and a CNT/S composite cathode was able to achieve a high specific energy density (≈589 Wh kg −1 ), a long life cycle (1 200 cycles) and quite high Coulombic efficiency (≈98%). Similarly, Tang et al demonstrated the deposition of a smooth Li silicide (Li x Si) coating to restructure an inhomogeneous Li surface to produce a uniform distribution of the Li + flux (Figure h). In situ optical microscopy observations confirmed that the Li x Si‐modified Li anode showed dendrite‐free Li dissolution/deposition behavior, whereas a bare Li electrode suffered with obvious dendrite growth.…”
Section: Strategies For Developing Stable LI Metal Anodesmentioning
confidence: 87%
“…h) Preparation of a Li x Si‐modified Li anode. Reproduced with permission . Copyright 2018 Wiley‐VCH.…”
Section: Strategies For Developing Stable LI Metal Anodesmentioning
confidence: 99%